Analysis of the Use of Digital Learning Media in Islamic Religious Subjects at SDN 48, Bengkulu City - Depi Helena; Niken Aprilia Azari; Wiwinda; Randi; Pahrozi Ahmad (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
The development of digital technology has brought changes in the world of education, including in the learning process of Islamic Religious Education (PAI) in elementary schools. This study aims to analyze the use of digital learning media in Islamic Religious Education subjects at SDN 48 Bengkulu City, determine the forms of digital media used, and identify factors that support and hinder its implementation. This study uses a qualitative approach with a descriptive research type. Data were collected through observation, interviews, and documentation. Data analysis techniques used include data reduction, data presentation, and drawing conclusions. The results show that digital media used in Islamic Religious Education learning include learning videos, PowerPoint presentations, digital images, and internet-based learning resources. The use of these media helps increase student attention, participation, and understanding of the material being studied. Supporting factors for the implementation of digital learning media include the availability of technological facilities, teacher ability to utilize technology, student enthusiasm, easy access to digital learning resources, and school support. Inhibiting factors include limited technological devices, internet network disruptions, differences in student abilities in using technology, teachers' limited time in preparing media, and technical constraints on learning devices. Thus, the use of digital learning media makes a positive contribution to the learning process of Islamic Religious Education at SDN 48 Bengkulu City.